Increased subchondral bone thickness in hips with cam-type femoroacetabular impingement. Issue 4 (July 2019) - Bieri, Martina; Beck, Martin; Limacher, Andreas; Wyatt, Michael C; Leunig, Michael; Jüni, Peter; Reichenbach, Stephan
Objectives: Increased thickness of subchondral acetabular bone with associated articular cartilage thinning in hips with femoroacetabular (FAI) cam impingement has been observed on magnetic resonance imaging (MRI). Dynamic attrition by the cam deformity moving into the acetabulum may potentiate trans-articular shear stresses thus causing these subchondral bone changes. We aimed to quantify the hypertrophic changes of subchondral acetabular bone in patients with cam-type FAI. Methods: MRI studies were performed on an asymptomatic population of young Swiss army recruits. Subjects underwent clinical examination and completed questionnaires before undergoing an MRI of the hip. Cam deformities were graded and the dimensions of the acetabular subchondral bone quantified. Univariate linear regression was used to determine the association between the presence of cam deformities and the degree of subchondral acetabular sclerosis. Results: There was a strong association between cam deformities and the thickness, area and shape of subchondral sclerosis. The main increase in hypertrophy was observed in the antero-superior acetabulum where impingement typically occurs. The subchondral sclerosis was 0.66 mm thicker in cam-type deformities than in hips without cam-type deformities (95% CI, 0.38–0.93, p value < 0.001). Conclusions: Mechanical stress in the antero-superior acetabular area is elevated in hips with a cam-type deformity. The study supports the concept that cam-type deformity induced stress leads to hypertrophy of subchondral acetabular bone in the area of impingement. This is collocated with the clinically observed cartilage damage caused by the cam mechanism.